2008
DOI: 10.1111/j.1365-2052.2008.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Using molecular markers and multivariate methods to study the genetic diversity of local European and Asian chicken breeds

Abstract: French and Asian subsets of chicken breeds were first analysed using 22 microsatellites and then compared to the AVIANDIV European set using 14 loci. Positive correlations were observed between F(IT) or F(ST) and typological values or variance of markers using the multivariate analysis mcoa. The first axis of the multivariate representation separated Asian from European breeds, revealing breeds with Asian ancestor. Using all or 14 loci, correct assignation rate was always higher than 93%. The Weitzman index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
63
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 21 publications
28
63
4
Order By: Relevance
“…The observed differences in the relationships between meat qualities traits among genotype could be related to the genetic variability of carcass traits that exist among those studied ecotypes (Tougan et al, 2013a). This result confirms the finding of Youssao et al (2010) who showed that indigenous chicken populations of Benin are characterized by a great genetic diversity than that reported for commercial lines chicken (Granevitze et al, 2007;Muchadeyi et al, 2007;Berthouly et al, 2008). In accordance with Havenstein et al (2003aHavenstein et al ( , 2003b, technological and nutritional meat quality depend on genotype.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 80%
“…The observed differences in the relationships between meat qualities traits among genotype could be related to the genetic variability of carcass traits that exist among those studied ecotypes (Tougan et al, 2013a). This result confirms the finding of Youssao et al (2010) who showed that indigenous chicken populations of Benin are characterized by a great genetic diversity than that reported for commercial lines chicken (Granevitze et al, 2007;Muchadeyi et al, 2007;Berthouly et al, 2008). In accordance with Havenstein et al (2003aHavenstein et al ( , 2003b, technological and nutritional meat quality depend on genotype.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 80%
“…CLEMENTINO et al (2010) andFONTEQUE et al (2014) found an average number of 9.6 and 12.4 alleles per locus, respectively, in studies with microsatellites in free range chickens from Brazil. Lower values than the results found in this study were also described by AL-QAMASHOUI et al (2014) - 8.4 (VANHALA et al, 1998;KYSER et al, 2000;ZHANG et al, 2002;HILLEL et al, 2003;TADANO et al, 2007;BERTHOULY et al, 2008;ROSÁRIO et al, 2009;CHATTERJEE et al, 2010;TADANO et al, 2012;WILKINSON et al, 2012). Normally, it is expected that the genetic variability of commercial chickens lines had been reduced because they are selected for quantitative traits (HILLEL et al, 2003).…”
Section: Resultscontrasting
confidence: 53%
“…On the basis of microsatellite information, African and Asian local chicken populations showed high genetic diversity [3,5,4,11]. It is interesting to note that by conserving such local breeds an important part of the gene pool is assumed to be conserved according to microsatellite data.…”
Section: Introductionmentioning
confidence: 99%